The association between season, day length, and temperature on clinical outcomes after cryopreserved embryo transfer - Correia, Katharine F B; Farland, Leslie V; Missmer, Stacey A; Racowsky, Catherine (Fertility and sterility, 2022)
To investigate whether there is an association between season, temperature, and day length at oocyte retrieval and/or embryo transfer (ET) and clinical outcomes in frozen ET cycles. Retrospective cohort study. Large academically affiliated research hospital. A total of 3,004 frozen ET cycles from 1,937 different women with oocyte retrieval and transfer between 2012 and 2017. None. Implantation, clinical pregnancy, spontaneous abortion, and live birth. Frozen ETs with oocyte retrieval dates in summer had 45% greater odds of clinical pregnancy (odds ratio [OR], 1.45; 95% confidence interval [CI], 1.15-1.82) and 42% greater odds of live birth (OR, 1.42; 95% CI, 1.13-1.79) compared with those with oocyte retrieval dates in winter. A 41% greater odds of clinical pregnancy (OR, 1.41; 95% CI, 1.16-1.71) and 34% greater odds of live birth (OR, 1.34; 95% CI, 1.10-1.62) were observed among transfers with an average temperature at oocyte retrieval in the highest tertile (17.2-33.3 °C) compared with those in the lowest tertile (-17.2-6.7 °C). There were no consistent associations between clinical outcomes and day length at oocyte retrieval or between season, day length, or temperature at transfer of thawed embryos. Warmer temperatures at oocyte retrieval are associated with higher odds of clinical pregnancy and live birth among frozen ET cycles. The consistent associations seen with oocyte retrieval dates and the lack of associations observed with ET dates suggest that any seasonality effects on in vitro fertilization success are related to ovarian function and not uterine receptivity.